The effectiveness of the writing clinic program in improving compliance with scientific articles and methodological standards - Alpiyendra, Dodi; Nelly, Jumni (Priviet Social Sciences Journal, 2026)
This study examines the journal writing clinic as a strategic approach to increase the academic capacity of the university community to produce scientific articles in accordance with national publication standards. Using qualitative descriptive methods through literature studies, observation of clinical activities, and analysis of training and mentoring documents, this study explains the basic concepts, implementation process, optimization strategies, and effectiveness of writing clinics in supporting the productivity of scientific publications of the participants. The results of the study show that the writing clinic functions as a systematic, directed, and collaborative guidance space, which provides technical assistance related to article structure, research methodology, journal style of cheating, as well as strengthening scientific argumentation, reference quality, and understanding publication ethics. Optimization strategies in the form of intensive workshops, individual mentoring, peer review, and gradual evaluation have been proven to improve the quality of participants' writing, while the success of the program is greatly influenced by the competence of the facilitators, the availability of literature, and the commitment of participants. Overall, journal writing clinics have proven to be effective instruments for academic development and have important implications for universities in designing sustainable mentoring models to improve the quality and quantity of scientific publications in Indonesia.